Social Pressure and Decision Making in the Workplace - Cindy Ramadhani Mamanik; Davina Zahwa Purbam; Sabri Tudar Sihotang (Journal of Global Islamic Economic Studies, 2024)
This study aims to explore the influence of social pressure on decision-making processes in the workplace, examining how pressures from supervisors, coworkers, and organizational culture affect individuals' decision-making behavior. The research adopts a library research method with a qualitative descriptive approach. Data is collected from various literature sources, such as books, articles, journals, and documents related to social pressure and its impact on decision-making in the workplace. Content analysis is used to interpret and evaluate the gathered data. The study identifies several forms of social pressure in the workplace, including obedience pressure from supervisors, peer pressure from coworkers, and the pressure to conform to organizational norms. These pressures can impact decision-making by encouraging individuals to prioritize social harmony over objective analysis. While social pressure can motivate collaboration, excessive pressure can negatively affect decision quality and contribute to stress and burnout. The study also highlights the need for organizations to create supportive environments that promote healthier decision-making processes.